2012
DOI: 10.1001/archophthalmol.2012.2270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Normal Human Foveal Development Using Optical Coherence Tomography and Histologic Examination

Abstract: Objective Assess outer retinal layer maturation during late gestation and early postnatal life using optical coherence tomography (OCT) and histology. Methods Thirty-nine subjects ranging from 32 weeks post-menstrual age (PMA) to 4 years were imaged using a hand held OCT (102 imaging sessions). Foveal images from 16 subjects (21 imaging sessions) were normal and evaluated for inner retinal excavation and presence of outer retinal reflective bands. Reflectivity profiles of central, parafoveal, and perifoveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 30 publications
3
84
1
1
Order By: Relevance
“…19 It is hypothesized that mechanical stretching of the retina caused by growth of the eye drives migration of the inner retinal layers away from the fovea. 24 The largest change in axial length (reflecting eye growth) occurs during the first 24 months of life, when the axial length reaches 90% of mean adult values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 It is hypothesized that mechanical stretching of the retina caused by growth of the eye drives migration of the inner retinal layers away from the fovea. 24 The largest change in axial length (reflecting eye growth) occurs during the first 24 months of life, when the axial length reaches 90% of mean adult values.…”
Section: Discussionmentioning
confidence: 99%
“…12,16,17 Foveal development has been reported to be completed between 11 months and 5 years of age. 12,13,18,19 In contrast, it has been shown that visual functions increase until adulthood, which has been attributed to maturation of the visual cortex. 20 The aim of this study was to determine the developmental time course and trajectories for each retinal layer at the fovea and define the contribution of each retinal layer to the development of normal vision in full-term infants and young children using HH-SDOCT.…”
mentioning
confidence: 99%
“…37,38 Instead, Tschopp et al 35 suggested that age differences in perimetry may be due to gradual maturation in selective visual attention, with the need to fixate a central fixation target causing a form of ''cognitive tunnel vision'' in younger children. The pattern of sensitivity estimates observed in the present study are consistent with this hypothesis, in that children's deficit was most pronounced at more eccentric locations (38 and 58) and smaller around the center (18,08).…”
Section: Sensitivitymentioning
confidence: 99%
“…We decided to evaluate two commercial platforms that are commonly used in human adult imaging, clinical research, and randomized clinical trials. [2][3][4] We chose a commercial hand-held portable platform approved for retinal imaging in pediatric human subjects 5,14,[20][21][22] and in basic animal research. [23][24][25] Furthermore, the largest ongoing randomized trial for age-related macular degeneration (AMD), the NEI-sponsored Age-Related Eye Disease Study 2, exclusively allows the Bioptigen SDOIS platform for its longitudinal, observational ancillary SDOCT study (AREDS2 Ancillary SDOCT Study).…”
Section: -10mentioning
confidence: 99%